The Effectiveness of Integrated Counseling on Pregnant Mothers to Improve Knowledge on Pregnant Mothers in Pematangsiantar City - Santi Nurida Br Nainggolan; R. Kintoko Rochadi; Zulhaida Lubis (Budapest International Research and Critics University, 2020)
Integrated counseling through lectures and booklets is an effort to increase knowledge on pregnant women in Pematangsiantar City. Second trimester pregnant women are the target to prevent children from starting in the womb as early as possible. The purpose of this study was to analyze the effectiveness of integrated lectures on pregnant women in increasing maternal knowledge. The type of research used in this study was quasi-experiment (quasy eperiment) with a pretest-posttest design. The number of samples is 20 people per group. Data analysis used the Independent-Sample T-Test. The results showed that there was the effectiveness of integrated counseling in the form of lectures and booklets on knowledge before and after giving lectures and booklets with an average value of knowledge 10.35 to 16.55 which increased with the value of p = 0.0001 and increase the average attitude value of 31.70 becomes 42.15 with a value of p = 0,0001. Need to add booklet media in the activities of pregnant women in pregnant women.